2017
DOI: 10.1017/cem.2017.355
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide survey on current management strategies of toddler’s fractures

Abstract: Our study is the first to identify nationwide variation in the management of toddler's fractures. This variation highlights the need for future research to compare the different management strategies to determine families' preferences and functional outcomes in children with these injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 25 publications
(28 reference statements)
3
25
0
Order By: Relevance
“…The majority of proven fractures were immobilised, while the majority of suspected fractures were treated with non-immobilisation. These findings are similar to those in reports from Canada and Scotland 5 11. However, in the USA, casting is more common 7 8…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The majority of proven fractures were immobilised, while the majority of suspected fractures were treated with non-immobilisation. These findings are similar to those in reports from Canada and Scotland 5 11. However, in the USA, casting is more common 7 8…”
Section: Discussionsupporting
confidence: 89%
“…Recommendations for treatment of minor tibial fractures vary from full above knee casting,6 above or below knee casting,7 splint, controlled ankle motion boot to no immobilisation; however, the evidence base underpinning these recommendations is scant based on surveys and retrospective case series 8–10. Practice varies within and between institutions 10 11. It is clear that these fractures heal well, and complications of immobilisation are not uncommon 7 10…”
Section: Introductionmentioning
confidence: 99%
“…37 Although rare, complications associated with cast immobilization include heel ulcers, pressure sores, skin breakdown, cellulitis, and prolonged limping. 23,26,37 Leg splint is an alternate treatment option, with no documented cases of failure. 23 The proposed advantages of splinting include: increased function of the lower limb, easier monitoring, and decreased need for clinical follow-up as the splint can be easily removed at home.…”
Section: Managementmentioning
confidence: 99%
“…This approach is reasonably common, as 1 Canadian study demonstrated 44% of emergency medicine physicians chose not to immobilize in the case of a negative initial radiograph and presumed clinical diagnosis of toddler's fracture. 37 Beyond the initial clinical treatment, another important consideration for the treating physician in the clinic or emergency department is the development of an appropriate follow-up plan. Most toddler's fractures can likely be treated primarily with reassurance and discussion of prognosis and healing.…”
Section: Managementmentioning
confidence: 99%
“…Patients with obvious fracture on radiographs should be placed into a long leg cast, but the management of suspected, occult fractures that are not visible on radiographs is controversial. Seguin et al surveyed 153 U.S. orthopaedists about their management of suspected occult toddler fractures and found that 44% of survey respondents treated the patient without a cast initially, 22% immobilized the leg in a short leg splint, and 14% immobilized the leg in a long leg cast 23 . At our institutions, these patients are immobilized in a long leg cast and follow-up radiographs are made in the office 2 to 3 weeks after initial presentation.…”
Section: Casting With or Without Closed Reductionmentioning
confidence: 99%